2016
DOI: 10.1093/nar/gkw639
|View full text |Cite
|
Sign up to set email alerts
|

Inter-sigmulon communication through topological promoter coupling

Abstract: Divergent transcription from within bacterial intergenic regions frequently involves promoters dependent on alternative σ-factors. This is the case for the non-overlapping σ70- and σ54-dependent promoters that control production of the substrate-responsive regulator and enzymes for (methyl)phenol catabolism. Here, using an array of in vivo and in vitro assays, we identify transcription-driven supercoiling arising from the σ54-promoter as the mechanism underlying inter-promoter communication that results in sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Gel retardation assay was carried out according to. 81 A 1,100 bp DNA fragment corresponding to the regulatory region upstream from hilA was generated using the primers hilA_prom_Fw and hilA_prom_Rev listed in Table S3B. 75 ng of the DNA probe was incubated at 4°C for 60 min with 1 unit of E. coli RNAP holoenzyme (New-England Biolabs) and increasing amounts (0.017 to 0.7 µg) of purified His-DksA in the Binding buffer [35 mM Tris-Ac (pH 7.9), 70 mM KAc, 5 mM MgAc 2 , 20 mM NH 4 Ac, 1 mM DTT].…”
Section: Methodsmentioning
confidence: 99%
“…Gel retardation assay was carried out according to. 81 A 1,100 bp DNA fragment corresponding to the regulatory region upstream from hilA was generated using the primers hilA_prom_Fw and hilA_prom_Rev listed in Table S3B. 75 ng of the DNA probe was incubated at 4°C for 60 min with 1 unit of E. coli RNAP holoenzyme (New-England Biolabs) and increasing amounts (0.017 to 0.7 µg) of purified His-DksA in the Binding buffer [35 mM Tris-Ac (pH 7.9), 70 mM KAc, 5 mM MgAc 2 , 20 mM NH 4 Ac, 1 mM DTT].…”
Section: Methodsmentioning
confidence: 99%
“…Although these two transient supercoiled domains may be relaxed by DNA topoisomerases or cancel each other by diffusion (13,14,16,24), they should have great influence on nearby DNA transactions, such as transcription. Indeed, several cases (25)(26)(27)(28)(29) demonstrated that transcription coupled DNA supercoiling (TCDS) 2 plays important roles in divergently coupled promoters/transcriptions in which two neighboring promoters initiate transcription in opposite directions. For example, in the ilvYC operon of E. coli, the ilvY promoter is divergently coupled to the ilvC promoter (28).…”
mentioning
confidence: 99%